Dignity and Posthumous Dignity: Respect for the Patient and the Deceased - Arriaga-Deza, Emma Vanesa (2020)
Objetive. The COVID-19 pandemic has caused a stir in the different system: health, economic and sociocultural around the world, this due to its characteristics so unique that they compare it to other great pandemics. Peru is no stranger to these circumstances that destabilize and alter tranquility and confront us with different ethical dilemmas. The dignity of the person intrinsic to his human condition, and which constitutes the basis of ethics, during times of crisis such as the one he is going through becomes more vulnerable, this being clearly reflected in the treatment given to patients , forgetting that they are people worthy of respect at all times and that this respect transcends all the data and examinations that belong to them, including their inert body in the event of death.